Hemophagocytic lymphohistiocytosis secondary to visceral leishmaniasis in children: case report and systematic review - Chen, Zhu; Gao, Yi; Zhang, Chaoyong; Mao, Junwen (Frontiers in Pediatrics, 2025)
BackgroundVisceral leishmaniasis (VL) can lead to complications such as hemophagocytic lymphohistiocytosis (HLH) in children. The clinical features of VL overlap with that of HLH, and thus the diagnosis of VL-induced HLH can be challenging for clinicians.MethodsWe describe two pediatric cases and systematically review all reported cases of pediatric VL-related HLH in literatures until May 2024.ResultsThe demographic characteristics, clinical manifestations, treatment and prognosis of our reported cases are presented. The systematic review included 29 articles with a total of 135 cases. More than half of the children (89/125, 71.2%) were under 3 years old, and 8.9% (n = 12/135) had specific epidemiological histories. The main clinical presentations were hypertriglyceridemia (34/45, 75.6%), hypofibrinogenemia (24/36, 66.7%), and hyperferritinemia (95/132, 72.0%). Bone marrow aspiration (BMA) analysis indicated positive evidence of leishmania infection in 84.7% (83/98) of cases, while 37.8% (14/37) of patients tested negative for leishmania on the first BMA smear. All patients were treated against leishmania with amphotericin B (76/135, 56.3%) or antimony (77/135, 57.0%), and 13.3% (n = 18/135) of patients received both medications, in which amphotericin B was used as rescue treatment. The prognosis was favorable, with the exception of two deaths.ConclusionsVigilance towards screening for leishmania infection induced HLH is imperative, particularly when there is a suspicious epidemiological history, ineffective chemotherapy, or prior to bone marrow transplantation. Early recognition, accurate diagnosis, and prompt treatment initiation can significantly alter the course of the disease and favor the prognosis in childhood with HLH secondary to VL.